Technology Commercialisation in a Developing Country: Current Condition and Its Challenge in Indonesia - Dhewanto, Wawan; Khoirul Umam, Khamdan (The Asian Journal of Technology Management (AJTM), 2009)
Innovation is considered the main engine of economic growth in both developed and developing countries. Despite the important role of innovation, little has been understood about technology transfer becoming a commercial success in developing countries, especially in the Indonesian context. The purpose of this paper is to identify technology commercialisation activities in Indonesia. Based on secondary data sources, an analysis of the current state regarding the issue is constructed. The findings in this paper suggest that technology commercialisation in Indonesia is initiated at the levels of university, government research institution, and corporate. This study provides insights for policy makers, business leaders, and university administrators into the appropriate roles of institutions and organisations in promoting and assisting technology commercialisation activities of their respective inventors.Key words: Technology commercialisation, developing country, university, government research institution, corporate